2021
DOI: 10.3389/fpsyt.2021.687546
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Associations Between Lifetime Use of Psychedelic Drugs and Psychometric Measures During the COVID-19 Confinement: A Transcultural Study

Abstract: Background: One of the main public health strategies adopted at the beginning of the COVID-19 pandemic consisted of implementing strict lockdowns to stop the transmission of the virus. Despite being an effective measure, the confinement and the associated social isolation create a stressful, potentially lengthy situations that has been proven to have several psychological consequences. Given the potential benefits that certain psychedelic drugs have shown for the treatment of psychological disorders, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 75 publications
(93 reference statements)
3
21
2
Order By: Relevance
“…These findings were distinctly different from those of a recent international study which showed that regular users of psychedelic drugs had less psychological stress compared to occasional users and non-users, suggesting that the use of psychedelics might either be a protective factor or that people with certain traits were more prone to frequently use psychedelic drugs (27). This difference could be ascribed to our study focusing on any use rather than regular use, or that PM users in the US comprise a distinctly different demographic group as compared to their international counterparts.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings were distinctly different from those of a recent international study which showed that regular users of psychedelic drugs had less psychological stress compared to occasional users and non-users, suggesting that the use of psychedelics might either be a protective factor or that people with certain traits were more prone to frequently use psychedelic drugs (27). This difference could be ascribed to our study focusing on any use rather than regular use, or that PM users in the US comprise a distinctly different demographic group as compared to their international counterparts.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings were distinctly different from a recent international study which showed that regular users of psychedelic drugs had less psychological stress compared to occasional users and non-users, suggesting that the use of psychedelics might either be a protective factor or that people with certain traits were more prone to frequently use psychedelic drugs (34). This difference could either be ascribed to our study focusing on any use rather than regular use, or that PM users in the US comprise a distinctly different demographic grouping than their international counterparts.…”
Section: Discussioncontrasting
confidence: 99%
“…The scientific information gathered to date suggests that ayahuasca has a good safety and tolerability profile (Bouso et al 2021) following acute administration in controlled settings (Riba et al 2001;Rocha et al 2021) and after prolonged ritual use (Barbosa et al 2012(Barbosa et al , 2016Bouso et al 2012;Gable 2007;Mello et al 2019). Observational evidence also suggests a low risk for abuse (Barbosa et al 2012(Barbosa et al , 2016Bouso et al 2012;Fábregas et al 2010;Gable 2007) and beneficial effects for substance-related disorders, mood and anxiety disorders, and improvement of general well-being (Argento et al 2019;Bouso et al 2012;Cruz and Nappo 2018;Gable 2007;Gonzalez et al 2021;Grob et al 1996;Horák, Hasíková, and Verter 2018;Lawn et al 2017;Ona et al 2019;Perkins et al 2021aPerkins et al , 2021bRévész et al 2021).…”
Section: Introductionmentioning
confidence: 99%